Oral history interview with C.J. Taylor, July 14, 2002 - Taylor, C.J. (Valdosta State University Archives and Special Collections, 2002)
Oral history interview with C.J. Taylor, July 14, 2002. Blackshear (Ga.). Fieldworker: Timothy C. Prizer. Audio file digitized from cassette tape. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. The contents are an occupational folklife analysis on C.J. Taylor’s life living and working in numerous turpentine camps. The interview focuses on several aspects of life in the camp, predominately on the sometimes harsh characteristics of woodsriders and bosses. Taylor is a Korean War veteran, and this is a recurrent topic as well.
1 electronic record(s) and derivatives. 2 audio file (wav, mp3) 1001910216 bytes. 01:34:39. 3 PDF documents (2 scans, jp2). 1.08 GB (1,163,245,328 bytes)
Keywords: Georgia; Oral histories; Sound recordings; Turpentine; Turpentining; Blackshear (Ga.); Naval stores; African Americans